Everyday life in Warsaw in the beginning phase of the first world war - Milewska, Marta (City and War, 2021)
After the outbreak of World War I, everyday life in Warsaw changed. The great war was remembered by the inhabitants of Warsaw as difficult years, in which they experienced a sense of uncertainty, fear and hunger. The lack of reliable information led to panic in the city and communication chaos. The aim of the article is to show various aspects of everyday life in the capital and the difficulties that resulted from the ongoing war. The article also presents the supply difficulties of the inhabitants of the capital and the problems of medical care. Part of the article contains content about the organization of self-help in Warsaw at the beginning of the First World War. Based on this information, it was possible to establish that thanks to the extensive structures of the Citizens’ Committee and the activities of other charity institutions, help reached the most impoverished ones.